Effect of foaming water dosage on mechanical properties of warm foamed asphalt mixture - He, Yan; Li, Haibo; He, Chuanping; Zhang, Yangpeng; Wang, Peng; Li, Pengfei (Frontiers in Materials, 2025)
This study investigated the impact of foaming water consumption on the mechanical properties of foam warm mix matrix asphalt mixture (FWMAM) and foam warm mix SBS-modified asphalt mixture (FWMAM-SBS) through comparative analysis with conventional hot mix matrix asphalt mixture (HMAM) and hot mix SBS-modified asphalt mixture (HMAM-SBS). The results showed that: The tensile strength ratio (TSR) of FWMAM showed no significant difference from HMAM, whereas HMAM-SBS exhibited slightly reduced TSR compared to FWMAM-SBS. The rutting resistance of FWMAM was superior to HMAM and enhanced progressively as the water consumption increased, while the anti-rutting performance of FWMAM-SBS was less affected by the foaming water consumption. The low-temperature cracking resistance of FWMAM was generally weaker than that of HMAM, while the opposite is true for FWMAM-SBS, with lower temperatures amplifying the influence of foaming water content. The master curve distribution characteristics of the FWMAM are consistent with those of the HMAM, and the water consumption is positively correlated with the modulus of the FWMAM and has a lower effect on the FWMAM-SBS at the conventional loading frequency. For fatigue life, both FWMAM and FWMAM-SBS outperform the corresponding hot-mix mixture. The fatigue life of FWMAM gradually decreased with increasing foaming water content, while FWMAM-SBS initially increased and then decreased, peaking at 2% water content, while fatigue life of FWMAM at low strain level conditions is roughly 1.2 times higher than that of the HMAM. Based on mechanical performance and foaming efficacy, optimal water consumption thresholds are proposed: ≤1% for matrix asphalt and ≤2% for SBS-modified asphalt.